House dust fungal communities’ characterization: a double take on the six by sixty by six project (6x60x6) - Amaro, Raquel (2017)
Background and objective(s): Fungi are a group microbes that are found with particular incidence in the indoor environment. Their direct toxicity or capability of generating toxic compounds has been associated with a large number of adverse health effects, such as infectious diseases, allergies and other toxic effects. House dust is a time integrative matrix easy to obtain and have been recommended for epidemiological studies on human exposure to environmental contaminants. This study aims to quantify and identify the fungal community on house dust samples collected using two different methodologies: active and passive sampling.